2014
DOI: 10.1302/0301-620x.96b7.31585
|View full text |Cite
|
Sign up to set email alerts
|

Athletic activity after lower limb arthroplasty

Abstract: In this systematic review, our aim was to explore whether or not patients are able to return to athletic activity following lower limb joint replacement. We also investigated any evidence as to whether participation in athletic activity post-joint replacement increases complications and reduces implant survival. A PubMed, Embase and Sports Discus search was performed using the MeSH terms 'Sport', 'Athletic', 'Athlete', 'Physical', 'Activity', 'Arthroplasty', 'Total Hip Replacement', 'Hip Resurfacing', 'Total K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Thus, higher rates of osteolysis and aseptic loosening should be expected with higher activity. In a recent systematic literature review, the relationship between revision rates, PE wear, and activity reported was analyzed [ 39 ]. The authors observed no increase in revision rates due to higher activity despite the fact that higher wear rates were verified for more active patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, higher rates of osteolysis and aseptic loosening should be expected with higher activity. In a recent systematic literature review, the relationship between revision rates, PE wear, and activity reported was analyzed [ 39 ]. The authors observed no increase in revision rates due to higher activity despite the fact that higher wear rates were verified for more active patients.…”
Section: Discussionmentioning
confidence: 99%
“…These include improved stability, low wearing bearing surfaces and improved proprioception 15 although it has been suggested that return to sporting activity post lower limb arthroplasty surgery is mainly determined by presurgical activity levels, BMI and age. 16 …”
Section: Discussionmentioning
confidence: 99%
“…15,18,29,31,50,54,66,70 However, in patients who wish to resume recreational and occupational activities after TKA, the high loads placed on the knee joint may result in chronic effusions and muscle dysfunction. This is especially true in patients who return to high-impact occupations that may preclude participation in recreational activities due to a mechanical overload of the joint that produces pain and swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Other reviews describe subjective expert opinion regarding the most appropriate activities after TKA. 22,29,54,66 However, the available evidence is low quality (level 3 or 4). One study focused solely on patients who resumed high-impact activities (tennis, aerobics, jogging, racquetball, squash), which represented only 4% of TKAs performed at 3 institutions over an 8-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation